Policing and war in Europe - Knafla, Louis A. (Criminal justice history, 2002)
Machine generated contents note: Introduction xi -- Louis A. Knafla -- Sir John Fielding, Sir Charles Whitworth, and the Westminster Night Watch Act, 1770-1775 1 -- Elaine A. Reynolds -- War and Crime in Napoleonic Italy, 1800-1814: Regeneration, Imperialism, and Resistance 21 -- Michael Broers -- The Felon and the Angel Copier: Criminal Identity and the Promise of Photography in Victorian England and Wales 53 -- Richard W. Ireland -- "Private Policing and the Workplace": The Worsted Committee and the Policing of Labor in Northern England, 1840-1880 87 -- Barry Godfrey -- Street, Beat, and Respectability: The Culture and Self-image of the Late Victorian and Edwardian Urban Policeman 107 -- Mark Clapson and Clive Emsley -- French Police, German Troops, and the Destruction of the Old District of Marseille, 1943 133 -- Simon Kitson -- "Trusted Servants of the Population": The Public Safety Branch and the German Police in the British Zone of Germany 145 -- David Smith -- Book Reviews -- Giorgia Alessi, Giustizia e polizia: il controllo di una capitale, Napoli 1779-1803 171 -- By Steven C. Hughes -- Steven C. Hughes, Crime, Disorder & the Risorgimento: -- The Politics of Policing in Bologna 173 -- By Michael Broers -- Geoffrey Morley, The Smuggling War: The Government's Fight against Smuggling in the 18th and 19th Centuries 176 -- By Paul Muskett -- F. Murray Greenwood, Legacies of Fear: Law and Politics in Quebec in the Era of the French Revolution 180 -- By Sylvio Normand -- Hereward Senior, Constabulary: The Rise of Police Institutions in Britain, the Commonwealth and the United States 183 -- By Louis A. Knafla -- Thomas H. Holloway, Policing Rio de Janeiro: Repression and Resistance in a 19th-Century City 184 -- By Marcos Luiz Bretas -- Elizabeth Cancelli, O Mundo da Violecia. A Policia da era Vargas 187 -- By Marcos Luiz Bretas -- Stefan Petrow, Policing Morals 189 -- By D. R. Welsh -- Barbara Weinberger, The Best Police in the World: An Oral History of English Policing from the 1930s to the 1960s 192 -- By Howard Taylor -- Charles Townshend, Making the Peace-Public Order and Public Security in Modern Britain 195 -- By Anne Mandeville -- Michel Berg&s, Le Syndicalisme policier en France (1880-1940) 198 -- By Simon Kitson -- Maria de Conceicao Ribeiro, Policia Politica no Estado Nova 1926-1945 200 -- By Lenor Sa